Elucidation of the Natural Function of Sophorolipids Produced by Starmerella bombicola - Veerle De Clercq; Sophie L. K. W. Roelants; Martijn G. Castelein; Sofie L. De Maeseneire; Wim K. Soetaert (Journal of Fungi, 2021)
The yeast Starmerella bombicola distinguishes itself from other yeasts by its potential of producing copious amounts of the secondary metabolites sophorolipids (SLs): these are glycolipid biosurfactants composed out of a(n) (acetylated) sophorose moiety and a lipid tail. Although SLs are the subject of numerous research papers and have been commercialized, e.g., in eco-friendly cleaning solutions, the natural function of SLs still remains elusive. This research article investigates several hypotheses for why S. bombicola invests that much energy in the production of SLs, and we conclude that the main natural function of SLs in S. bombicola is niche protection: (1) the extracellular storage of an energy-rich, yet metabolically less accessible carbon source that can be utilized by S. bombicola upon conditions of starvation with (2) antimicrobial properties. In this way, S. bombicola creates a dual advantage in competition with other microorganisms. Additionally, SLs can expedite growth on rapeseed oil, composed of triacylglycerols which are hydrophobic substrates present in the yeasts’ environment, for a non-SL producing strain (Δcyp52M1). It was also found that—at least under lab conditions—SLs do not provide protection against high osmotic pressure prevalent in sugar-rich environments such as honey or nectar present in the natural habitat of S. bombicola.